Impact of Weather Types on Weather Research and Forecasting Model Skill for Temperature and Precipitation Forecasting in Northwest Greece - Dimitrios C. Chaskos; Christos J. Lolis; Vassiliki Kotroni; Nikolaos Hatzianastassiou; Aristides Bartzokas (Atmosphere, 2024)
The accuracy of the Weather Research and Forecasting (WRF) model’s predictions for air temperature and precipitation in northwestern Greece varies under different weather conditions. However, there is a lack of understanding regarding how well the model performs for specific Weather Types (WTs), especially in regions with a complex topography like NW Greece. This study evaluates the WRF model’s ability to predict 2 m air temperature and precipitation for 10 objectively defined WTs. Forecasts are validated against observations from the station network of the National Observatory of Athens, focusing on biases and skill variation across WTs. The results indicate that anticyclonic WTs lead to a significant overestimation of early morning air temperatures, especially for inland stations. The precipitation forecast skill varies depending on the threshold and characteristics of each WT, showing optimal results for WTs where precipitation is associated with a combination of depression activity, and orographic effects. These findings indicate the need for adjustments based on WT in operational forecasting systems for regions with similar topographical complexities.